Japanese Constitutional Revisionism and Civic Activism - Hardacre, Helen (Lexington Books, 2021)
Japanese Constitutional Revisionism and Civic Activism is a volume that examines the history of Japan's constitutional debates, key legal decisions and interpretations, history and activism, and activists' ties to party politics and fellow activists overseas.